The Maitland quarto: a new edition of Cambridge, Magdalene college, Pepys library MS 1408 - Martin, Joanna M. (Boydell & Brewer, 2015)
The Maitland Quarto is a paper manuscript held in the collections of the Pepys Library, Magdalene College, Cambridge, where it is MS 1408. It contains 95 poems in 138 leaves, copied in a mixture of secretary and italic scripts, probably all the work of one hand. All but two of these poems appear to be of Scots origin, though several have English or continental sources. The first folio of the manuscript is inscribed twice with the date 1586 and the name of Marie Maitland, indicating that it was copied in the circle of the Maitlands of Lethington, a family of lowland lairds who had become increasingly influential in royal administration during the sixteenth century. Marie Maitland was one of four daughters of Sir Richard Maitland of Lethington, a privy counsellor, royal commissioner, Lord of Session, and keeper of the great seal of Scotland: she is explicitly addressed in two poems in the manuscript. Some of John Maitland’s vernacular poems and those of Richard Maitland are contained in the Quarto along with a number of poems attributed to members of what was presumably the wider Maitland circle including the scholar and principal of King’s College Aberdeen, Alexander Arbuthnot; the courtier poet Alexander Montgomerie; and musicians Thomas and Robert Hudson. There is also one poem attributed to ‘Jacobus Rex’ (James VI) and a substantial body of unattributed and often unique verse on a range of themes, amatory, religious and political, probably written by family members and associates. Amongst these we find the earliest example of a Country House poem from the British Isles, a Sapphic love poem, and examples of Calvinist verse.